Game Edukasi Pengenalan Hewan Endemik Pulau Kalimantan Berbasis Android Menggunakan Construct 2 - Irwan, Gt; Rusdiana, Lili (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2024)
The purpose of this research is to make an Android-based educational game to introduce endemic animals to the island of Borneo using Construct 2, the results of which can be useful for the community to increase knowledge about endemic animals on the island of Borneo. This educational game has a game of arranging animal name letters and multiple choice questions which are expected to hone the user's memory of endemic animals on the island of Borneo. The method used in this research is the Multimedia Development Life Cycle (MDLC) method are concept, design, material collecting, assembly, testing, and distribution. In this study, Black Box Testing was carried out and the result was that the game system ran well and its functionality could work smoothly. Based on the results of the questionnaire which was filled in by 30 respondents, the Endemic Animals of Kalimantan game was in the interval of strongly agreeing with the questionnaire and application category with a percentage of 85.42%, which means that the Endemic Animals of Kalimantan game is in demand by the public.